"Protección catódica con corriente impresa de aceros estructurales ASTM A-36, recubiertos con pintura y enterrados en suelos franco-arenosos húmedos" - Quevedo Narváez, Alejandro Ausberto (2017)
ABSTRACT In the present research the effect of the cathodic current applied on the corrosion rate of steels ASTM A 36, when they were painted with anti-corrosive paint system and buried in sandy loam soil moist was evaluated (predominance of sand, adequate moisture retention). For the results has been used, painted steel specimens of dimensions 100 x 50 x 6mm and has been left uncovered a side area of 600mm (6 X 100 mm) Simulating paint defects and scratches that occur during handling, welding, etc. of these steels when they are part of structures, also controlled current was supplied using a current transformer rectifier and the experimental circuit also allowed specimens buried in the ground of the UNT campus. The salient results indicate that the specimens unprotected recorded an electrochemical potential of -493mV (relative to the electrode copper / copper sulphate) and corrosion rate 114.19 μ/year, while when current is applied in a range of 5.3369 mA/m2, to an electrochemical potential -1249 mA (relative to the electrode copper / copper sulphate) was able to reduce the corrosion rate to a value of 1.423 which is equivalent to a decrease of 98% compared to the unprotected condition.